Design of cost management systems - Cooper, Robin (Prentice Hall Saddle RiverUS, 1999)
Introduces concepts of cost and performance measurement and presents a 4-stage model of cost system evolution. Looks at limitations of traditional costing systems for serving managerial purposes. Provides comprehensive treatment of activity-based costing (ABC) and activity-based management (ABM). Describes how the ABC system can be used as the foundation for budgeting an organization's future expenses and resource supply. Uses case examples to illustrate how the concepts have been applied in practice.